2017
DOI: 10.1016/j.anbehav.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Diet alters Drosophila melanogaster mate preference and attractiveness

Abstract: Diet alters Drosophila melanogaster mate preference and attractiveness Animals decide which potential mate to pair with based on their subjective evaluation of each candidate mate's attractiveness. Attractiveness and its perception are plastic traits, dependent upon genetic and environmental factors. When evaluating mate attractiveness, in some cases animals make predictive judgements of mate reproductive potential, or fitness, based on the mate's condition. Diet, a fluctuating environmental factor, influences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 134 publications
0
27
1
Order By: Relevance
“…These females also had altered CHC profiles. High fat-fed females are also more fecund 393 (Schultzhaus et al, 2017). However, Lin and colleagues (2018) found that females that ate high 394 yeast diet were heavier, more fecund, less immobile, had shorter lifespans, and had different 395 CHC profiles, but were also more attractive to males than low yeast-fed females, or than high 396 yeast-fed mutant females (hypomorphic for insulin peptides) or oenocyte-specific gene 397 disruption of insulin signaling.…”
mentioning
confidence: 99%
“…These females also had altered CHC profiles. High fat-fed females are also more fecund 393 (Schultzhaus et al, 2017). However, Lin and colleagues (2018) found that females that ate high 394 yeast diet were heavier, more fecund, less immobile, had shorter lifespans, and had different 395 CHC profiles, but were also more attractive to males than low yeast-fed females, or than high 396 yeast-fed mutant females (hypomorphic for insulin peptides) or oenocyte-specific gene 397 disruption of insulin signaling.…”
mentioning
confidence: 99%
“…The high degree of plasticity in mating-related traits shown by male Drosophila is now well established (Churchill et al, 2019;Davies et al, 2019;Droney, 1998;Fricke et al, 2008;Jensen et al, 2015;Lefranc and Bungaard, 2000;Lüpold et al, 2010;Morimoto and Wigby, 2016;Ormerod et al, 2017;Schultzhaus et al, 2017). Variation in these traits is highly sensitive to conspecific male density in a manner which suggests that males adjust investment in anticipation of the intensity of sperm competition they are likely to encounter during mating ).…”
Section: Discussionmentioning
confidence: 99%
“…For the purposes of this study, wildtype female flies are used throughout in order to isolate any potential effects of the adp 60 mutation and obesity on male courtship decisions. Previous studies have shown that wildtype male flies fed a high-fat diet show no effect of the resulting obesity on reproductive behaviors if fed the high-fat diet throughout development (Schultzhaus et al 2017), but wildtype male flies do show reductions in some aspects of courtship if fed a high-fat diet only as an adult (Schultzhaus et al 2018). In both cases, however, copulation rate is not affected.…”
Section: Introductionmentioning
confidence: 96%
“…While much is known about the metabolic consequences due to the loss of the adipose gene, little is known about how the adp 60 mutation affects reproductive behaviors. Previous studies have characterized reproductive behaviors in flies with other metabolic perturbations such as wildtype flies with diet-induced obesity (Schultzhaus et al, 2017(Schultzhaus et al, , 2018, and characterizing the courtship of the adp 60 mutant, would complement these studies.…”
Section: Introductionmentioning
confidence: 99%